First Aid Guidelines for Environmental Topics: Educational Approach and Adaptation (International Journal of First Aid Education)
Extreme environmental conditions and exposure to very high or low temperatures, particularly when this happens quickly, can lead to severe illness and injury. As the climate changes and temperature differences become more pronounced, these instances are likely to increase. First aid education which deals with environmental conditions is particularly important in circumstances where people are unprepared, more vulnerable due to age or have existing medical conditions. Remoteness or inaccessibility to medical care also increases vulnerability. This paper reviews a selection of the environmental topics covered in the International First Aid, Resuscitation and Education Guidelines 2020 (IFRC, 2020) which seek to blend clinical first aid evidence with educational evidence, principles and expertise. Covering Hyperthermia, Dehydration, Hypothermia, Frostbite, Altitude Sickness, and Motion Sickness, we provide educational and adaptation interpretation in different contexts, stimulate debate and identify gaps. We also review how the 2020 Guidelines viewed these topics through the lens of the Chain of Survival Behaviors and identify the most pertinent stages in that chain to focus learning on these topics. The 2020 Guidelines emphasize the need for content and educational adaptation according to the learner, which is central to these topics. First aid instructors and program designers need to frame action relevant to their audience and local needs. The teaching of environmental first aid topics should be contextualized to the local geography, legal requirements, culture and behaviors of the learners and their context. For these topics, we conclude that facilitation tips for environmental conditions requiring first aid should focus on prevention and helping learners to recognize early warning signs of the different conditions so they can take preventative action before serious illness sets in. الإرشادات التوجيهية للإسعافات الأولية لمواضيع الخاصة بالبيئة: التعليم والتكييف الظروف المناخية القاسية والتعرض لدرجات الحرارة المرتفعة أو المنخفضة جداً، خصوصاً عند التعرض لها بسرعة، قد يؤدي إلى الإصابة ومرض خطير. مع زيادة التغير المناخي والتغيير في درجات الحرارة، فمن المرجح أن تزداد هذه الإصابات. يعد تعليم الإسعافات الأولية الخاصة بالتعامل مع التغيرات المناخية مهماً في الظروف التي يكون في الناس غير مستعدين، وأكثر عرضة نتيجة للتقدم في السن أو إصابتهم بمشاكل صحية مسبقة. كما أن الحياة في الضواحي وعدم إمكانية الوصول للرعاية الصحية ترفعان من احتمالية تعرضهم للإصابة. هذه الورقة تراجع مجموعة من المواضيع البيئية المتضمنة في دليل الإسعافات الأولية والإنعاش والتعليم 2020، (الإتحاد الدولي لجمعيات الهلال والصليب الأحمر 2020) والتي تسعى لدمج  أدلة الإسعافات الأولية الكلينيكية مع الأدلة التعليمية، والمبادئ والخبرات. وتغطية مواضيع متعددة: كارتفاع درجة حرارة الجسم، الجفاف، انخفاض درجة حرارة الجسم، ضربة السقيع (قضمة السقيع)، داء المرتفعات، دوار الحركة، نحن نقدم تفسيراً علمياً وتعليلاً في سياقات مختلفة، لتحفيز النقاش وإيجاد الثغرات. ونحن أيضا في صدد مراجعة كيفية عرض دليل إرشادات سنة 2020 لهذه المواضيع من منظور سلسلة سلوكيات النجاة، وتحديد المراحل الأكثر أهمية في هذه السلسلة لتركيز التعلم على هذه المواضيع. يؤكد دليل إرشادات 2020 على الحاجة للمحتوى والتكيف التعليمي حسب المتعلم، والذي يعتبر أساسي في هذه المواضيع. يحتاج مدربي الإسعاف الأولي ومصممي البرامج إلى إطار للعمل ذا صلة بالجمهور المستهدف والاحتياج المحلي. يجب أن يوضع تعليم الإسعافات الأولية البيئية في سياق الطبيعة الجغرافية المحلية، والاحتياجات القانونية، وثقافة وسلوك المتعلمين في واقعهم المحلي. ختاما، نستنتج أن نصائح التيسير للظروف البيئية المتطلبة للإسعافات الأولية، يجب أن تركز على الوقاية ومساعدة المتعلمين على الانتباه لعلامات الإنذار المبكرة للمشاكل المختلفة، لكي يتمكنوا من أخذ الإجراءات الوقاية قبل الإصابة